The Influence of Understanding, Religiosity, and Culture on the Frugal Living Behavior of Generation Z in North Sumatra - Miranda Panjaitan; Marliyah Marliyah; Juliana Nasution (Indonesian Journal of Islamic Economics and Finance, 2026)
This study examines the influence of understanding, religiosity, and culture on frugal living behavior among Generation Z in North Sumatra. The study addresses the increasing relevance of frugal living amid rising living costs, digital consumerism, and economic uncertainty. The novelty of this research lies in the integration of cognitive, religious, and socio-cultural dimensions to explain frugal living behavior within the context of Generation Z in North Sumatra. A quantitative approach with a causal associative design was employed. Data were collected from 100 respondents using purposive sampling and analyzed through multiple linear regression. The findings indicate that understanding, religiosity, and culture positively and significantly affect frugal living behavior, both partially and simultaneously. Culture was identified as the most dominant factor influencing frugal living practices. The model explains 65.5% of the variation in frugal living behavior. These findings imply that promoting sustainable financial behavior among Generation Z requires not only improving financial understanding but also strengthening religious values and cultural norms that encourage simplicity, self-control, and responsible consumption. This study contributes to the literature on behavioral economics and Islamic economics related to sustainable consumption behavior among young generations.